Stakeholder Management Innovation in the Utilization of Right-of-Way on Major Arterial Roads in Bogor Regency - Ayu Permata Pekerti; Anang Muftiadi; Emma Rochima (Dinasti Publisher, 2025)
The development of major arterial roads and pedestrian infrastructure in the Cibinong Raya area to prepare for hosting the U-20 World Cup in 2023, is a leading program that uses up to 30% of the Bogor Regency infrastructure budget. Development with a large budget requires appropriately applied stakeholder management of infrastructure assets, through supervision and control of road assets accommodated in the licensing activities for using the right-of-way, to reduce the risk of physical damage to assets due to violations. The Result-Based Management Model was used to evaluate the control of asset utilization in providing technical recommendations for right-of-way utilization. Then, through ordinal scale weighting followed by in-depth interviews, an innovation model for stakeholder management risk control was obtained that is appropriate for the use of right-of-way on major arterial roads in Bogor Regency. The weighting of the stakeholder management indicators showed that the risk control aspect was the weakest element so it was necessary to emphasize the integration of the Risk Control function into each management indicator.